Liquid preservative for concrete resistant to high-concentration sulfate corrosion and preparation method thereof

A liquid preservative combining anhydrous salts and nano materials with hydrophobic and water-reducing agents addresses the inefficacy of existing preservatives in high-concentration sulfate environments, improving concrete's resistance and durability by reducing water absorption and enhancing density.

CN117886543BActive Publication Date: 2024-12-17JIANGSU SOBUTE NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211736262.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2024-12-17
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

Existing anti-sulfate preservatives are ineffective in high-concentration sulfate environments (above 100,000 mg/L) and face challenges with accuracy, dispersion uniformity, and cost in medium and low concentration sulfate environments.

Method used

A liquid preservative for concrete comprising a combination of anhydrous aluminum sulfate or magnesium sulfate, nano silicon dioxide or aluminum oxide, epoxy-modified polysiloxane or amino-modified polyether siloxane, and polycarboxylate or aminosulfonate water reducing agents, mixed in specific proportions to enhance resistance to high-concentration sulfate corrosion.

Benefits of technology

The liquid preservative significantly reduces water absorption and improves concrete density, ensuring effective resistance to high-concentration sulfate corrosion while maintaining accurate measurement and uniform dispersion, thus enhancing concrete durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004029426250000021
    Figure BDA0004029426250000021
  • Figure BDA0004029426250000091
    Figure BDA0004029426250000091
  • Figure BDA0004029426250000101
    Figure BDA0004029426250000101
Patent Text Reader

Abstract

The present invention belongs to the technical field of improving the durability of concrete, and in particular discloses a liquid preservative for concrete that resists high-concentration sulfate erosion and a preparation method thereof. The liquid preservative adopts a dense component and a hydrophobic component to synergistically act to effectively reduce the transmission rate of the corrosive medium and improve the resistance of the concrete matrix to sulfuric acid erosion. It has the characteristics of improving the density of concrete and significantly reducing the water absorption rate of concrete, and has a significant effect on improving the resistance of concrete to high-concentration sulfate erosion, and the resistance to sulfate concentration is as high as at least 100,000 mg / L. In addition, compared with the powdered preservative used in the prior art, the liquid agent method also improves the accuracy of measurement and the uniformity of dispersion, and is friendly to the environment and construction personnel and non-polluting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of concrete durability improvement, and in particular, relates to a liquid preservative for concrete that is resistant to high-concentration sulfate corrosion and a preparation method thereof. Background Art

[0002] my country has a vast territory. With the increase of national infrastructure investment, the durability of concrete structures faces challenges in various service environments. Sulfate corrosion of concrete is common in my country. The expansion corrosion of gypsum rock layers and saline soil in the west, saline soil in the east, and various chemical sulfate acid waste liquids in tunnels in the west. Sulfate erosion is caused by sulfate or SO4 in the environment. 2- It invades the concrete to form salt crystals, or reacts chemically with some solid components of cement paste to generate some insoluble salts. The salt crystals or insoluble salts formed absorb a large amount of water to expand in volume, forming expansion internal stress. When the expansion internal stress exceeds the tensile strength of concrete, it will lead to the destruction of concrete. In addition, the chemical reaction can also dissolve or decompose components such as CH and CSH in hardened cement, resulting in rapid loss of concrete strength and bonding properties, and ultimately leading to corrosion and spalling of concrete, or even structural damage.

[0003] In the current standards and specifications of my country, the environmental categories and environmental action levels of sulfate chemical corrosion environments are divided. The upper limit of sulfate ion concentration in water corresponding to the most serious chemical corrosion environment V-E in the national standard GB / T 50476-2019 "Concrete Structure Durability Design Code" is 10000mg / L, and the upper limit of sulfate ion concentration in soil (water-soluble value) is 15000mg / L; the water-soluble sulfate ion concentration in the most severe environment of the China Association for Engineering Construction Standardization T / CECS 607-2019 "Technical Specifications for Application of Corrosion-Resistant Concrete in Saline Soil Environment" is 15000mg / L; the upper limit of sulfate ion concentration in water corresponding to the most serious chemical corrosion environment VI-E in the industry standard JTG / T3310-2019 "Highway Engineering Concrete Structure Durability Design Code" is 20000mg / L, and the upper limit of sulfate ion concentration in soil (water-soluble value) is 30000mg / L. From the current standards and specifications for the range of sulfate chemical corrosion environment action levels, it can be seen that 30,000 mg / L is the upper limit of the sulfate ion concentration action level. However, geological survey reports of many projects in the muddy gypsum rock formation in Chengdu, Sichuan, show that the sulfate ion concentration (water-soluble value) exceeds 100,000 mg / L, far exceeding the current standard definition of sulfate ion concentration. In response to such a harsh environment, strong and effective measures must be taken for concrete structures to ensure the safety and durability of concrete structures.

[0004] There are two main ways to improve the sulfate corrosion resistance of existing concrete: (1) Use sulfate-resistant cement to improve the corrosion resistance of concrete. Traditional sulfate corrosion is caused by the formation of calcium sulfonate, which causes expansion and cracking. Studies have shown that a high content of C3A in cement clinker can lead to the formation of calcium sulfonate, which causes the hardened cement paste to expand during sulfate corrosion. The content of C3A in sulfate-resistant cement is limited to ≤5.0%. Although sulfate-resistant cement can inhibit calcium sulfonate sulfate corrosion to a certain extent, this method has the disadvantages of high cost, poor effect under dry and wet systems, and poor concrete matrix impermeability. (2) Apply protective materials or add functional additives. External protective materials generally involve brushing a layer of waterproof material on the outer surface of concrete to isolate external corrosive ions from entering the concrete matrix. This method is costly and not feasible for cast-in-place pile foundation concrete; the addition of functional additives generally uses anti-sulfate preservatives, which are mostly split products with the main components of expansion components and compacting components. They slow down the transmission rate of sulfate ions by increasing the density, but the measurement accuracy and dispersion uniformity of such powdered preservatives are difficult to control and guarantee in actual production applications; internal addition of hydrophobic materials can improve the hydrophobicity of the concrete surface, reduce the water absorption rate of the concrete matrix, and thus reduce the transmission rate of corrosive ions.

[0005] In the past, anti-sulfate preservatives for concrete were mostly used in medium and low concentration sulfate environments (sulfate content generally does not exceed 10,000 mg / L), and there was little research on the super-standard sulfate environment like the muddy gypsum rock formations in the Chengdu area. Summary of the invention

[0006] In view of the drawback that existing anti-sulfate preservatives cannot play a good role in high-concentration sulfate corrosion environments (generally exceeding 100,000 mg / L), the present invention provides a liquid preservative for concrete that resists high-concentration sulfate corrosion and a preparation method thereof. The liquid preservative uses a dense component and a hydrophobic component to synergistically reduce the transmission rate of the corrosive medium and improve the concrete matrix's resistance to sulfuric acid corrosion. The product is mainly used in high-concentration sulfate corrosion environments and aims to provide a concrete durability improvement technology that increases concrete's resistance to harmful ion corrosion.

[0007] The present invention specifically adopts the following technical solutions:

[0008] A liquid preservative for concrete that resists high-concentration sulfate corrosion, comprising the following components that are uniformly mixed in liquid form according to mass fraction:

[0009]

[0010]

[0011] Furthermore, the expansion component is one of anhydrous aluminum sulfate and anhydrous magnesium sulfate or a mixture of the two, wherein the expansion component is a 5% solid solution.

[0012] Furthermore, the dense component is one of nano silicon dioxide and nano aluminum oxide or a mixture of the two, and the particle size of the nano material is less than 50 nm.

[0013] Furthermore, the hydrophobic component is one or a mixture of at least two of epoxy-modified polysiloxane, amino-modified polyether siloxane, and tridecafluorooctyl triethoxysilane.

[0014] Furthermore, the water reducing component is a mixture of one or both of a polycarboxylate water reducing agent and an aminosulfonate water reducing agent.

[0015] The preparation method of the liquid preservative for concrete resistant to high-concentration sulfate corrosion provided by the present invention comprises the following specific steps:

[0016] (1) Add water to the reaction device, and control the temperature to be between 30°C and 50°C, add the compacting component and the swelling component to the water in sequence, and stir at a stirring speed of 300 rpm to 600 rpm for 30 min to 45 min;

[0017] (2) adding a hydrophobic component to the mixture after stirring in step (1), and then continuing to stir for 1 hour;

[0018] (3) Add a water-reducing component to the mixture after stirring in step (2), control the temperature to 25° C. to 40° C., and stir for 20 min to 40 min to obtain the liquid preservative of the present invention.

[0019] The present invention provides a liquid preservative for concrete that resists high-concentration sulfate corrosion, which has the characteristics of improving the density of concrete and significantly reducing the water absorption rate of concrete, and has a significant effect on improving the concrete's resistance to high-concentration sulfate corrosion. In addition, compared with the powdered preservative used in the prior art, the liquid agent method also improves the accuracy of measurement and the uniformity of dispersion, and is friendly to the environment and construction personnel, and is non-polluting. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1

[0022] This embodiment provides a liquid preservative for concrete that resists high-concentration sulfate corrosion, which is a liquid mixture comprising the following components and weight percentages:

[0023] Expansive component anhydrous aluminum sulfate: 1.0%, dense component nano silicon dioxide: 20.0%, hydrophobic component epoxy modified polysiloxane: 20.0%, water reducing component polycarboxylic acid water reducing agent: 8.0%, water: 51.0%.

[0024] It is prepared by the following method:

[0025] (1) Add water to the reaction device, control the water temperature to 40°C, add the compacting component and the swelling component to the water in sequence, and stir at a stirring speed of 450 r / min for 40 min;

[0026] (2) adding a hydrophobic component to the mixture after stirring in step (1), and then continuing to stir for 1 hour;

[0027] (3) Add a water-reducing component to the mixture after stirring in step (2), control the temperature to 30° C., and stir for 20 minutes to obtain a first liquid preservative F1.

[0028] Example 2

[0029] This embodiment provides a liquid preservative for concrete that resists high-concentration sulfate corrosion, which is a liquid mixture comprising the following components and weight percentages:

[0030] The expansion component is anhydrous aluminum sulfate: 5.0%, the compacting component is nano-silica: 20.0%, the hydrophobic component is epoxy-modified polysiloxane: 20.0%, the water-reducing component is polycarboxylic acid water-reducing agent: 8.0%, and water: 47.0%.

[0031] It is prepared by the following method:

[0032] (1) Add water to the reaction device, control the water temperature to 40°C, add the compacting component and the swelling component to the water in sequence, and stir at a stirring speed of 450 r / min for 40 min;

[0033] (2) adding a hydrophobic component to the mixture after stirring in step (1), and then continuing to stir for 1 hour;

[0034] (3) Add a water-reducing component to the mixture after stirring in step (2), control the temperature to 30° C., and stir for 20 minutes to obtain a second liquid preservative F2.

[0035] Example 3

[0036] This embodiment provides a liquid preservative for concrete that resists high-concentration sulfate corrosion, which is a liquid mixture comprising the following components and weight percentages:

[0037] The expansion component is anhydrous magnesium sulfate: 5.0%, the compaction component is nano-alumina: 10.0%, the hydrophobic component is amino-modified polyether siloxane: 20.0%, the water-reducing component is polycarboxylic acid water-reducing agent: 8.0%, and water: 57.0%.

[0038] It is prepared by the following method:

[0039] (1) Add water to the reaction device, control the water temperature to 40°C, add the compacting component and the swelling component to the water in sequence, and stir at a stirring speed of 450 r / min for 45 minutes;

[0040] (2) adding a hydrophobic component to the mixture after stirring in step (1), and then continuing to stir for 1 hour;

[0041] (3) Add a water-reducing component to the mixture after stirring in step (2), control the temperature to 40° C., and stir for 40 minutes to obtain a third liquid preservative F3.

[0042] Example 4

[0043] This embodiment provides a liquid preservative for concrete that resists high-concentration sulfate corrosion, which is a liquid mixture comprising the following components and weight percentages:

[0044] The expansion component is anhydrous magnesium sulfate: 5.0%, the compaction component is nano-alumina: 25.0%, the hydrophobic component is amino-modified polyether siloxane: 20.0%, the water-reducing component is polycarboxylic acid water-reducing agent: 10.0%, and water: 42.0%.

[0045] It is prepared by the following method:

[0046] (1) Add water to the reaction device, control the water temperature to 45°C, add the compacting component and the swelling component to the water in sequence, and stir at a stirring speed of 400 r / min for 60 min;

[0047] (2) adding a hydrophobic component to the mixture after stirring in step (1), and then continuing to stir for 1 hour;

[0048] (3) Add a water-reducing component to the mixture after stirring in step (2), control the temperature to 35° C., and stir for 35 minutes to obtain a fourth liquid preservative F4.

[0049] Example 5

[0050] This embodiment provides a liquid preservative for concrete that resists high-concentration sulfate corrosion, which is a liquid mixture comprising the following components and weight percentages:

[0051] Expansion component anhydrous magnesium sulfate: 5.0%, dense component nano alumina: 20.0%, hydrophobic component tridecafluorooctyl triethoxysilane: 10.0%, water reducing component aminosulfonate water reducing agent: 8.0%, water: 57.0%.

[0052] It is prepared by the following method:

[0053] (1) Add water to the reaction device, control the water temperature to 40°C, add the compacting component and the swelling component to the water in sequence, and stir at a stirring speed of 450 r / min for 40 min;

[0054] (2) adding a hydrophobic component to the mixture after stirring in step (1), and then continuing to stir for 1 hour;

[0055] (3) Add a water-reducing component to the mixture after stirring in step (2), control the temperature to 30° C., and stir for 20 minutes to obtain a fifth liquid preservative F5.

[0056] Example 6

[0057] This embodiment provides a liquid preservative for concrete that resists high-concentration sulfate corrosion, which is a liquid mixture comprising the following components and weight percentages:

[0058] Expansion component anhydrous magnesium sulfate: 5.0%, dense component nano alumina: 20.0%, hydrophobic component tridecafluorooctyl triethoxysilane: 25.0%, water reducing component aminosulfonate water reducing agent: 8.0%, water: 42.0%.

[0059] It is prepared by the following method:

[0060] (1) Add water to the reaction device, control the water temperature to 35°C, add the compacting component and the swelling component to the water in sequence, and stir at a stirring speed of 500 r / min for 30 min;

[0061] (2) adding a hydrophobic component to the mixture after stirring in step (1), and then continuing to stir for 1 hour;

[0062] (3) Add a water-reducing component to the mixture after stirring in step (2), control the temperature to 40° C., and stir for 30 minutes to obtain a sixth liquid preservative F6.

[0063] Example 7

[0064] This embodiment provides a liquid preservative for concrete that resists high-concentration sulfate corrosion, which is a liquid mixture comprising the following components and weight percentages:

[0065] Expansion component anhydrous aluminum sulfate: 5.0%, dense component nano silicon dioxide: 20.0%, hydrophobic component amino modified polyether siloxane: 20.0%, water reducing component polycarboxylic acid water reducing agent: 5.0%, water: 50.0%.

[0066] It is prepared by the following method:

[0067] (1) Add water to the reaction device, control the water temperature to 40°C, add the compacting component and the swelling component to the water in sequence, and stir at a stirring speed of 450 r / min for 45 minutes;

[0068] (2) adding a hydrophobic component to the mixture after stirring in step (1), and then continuing to stir for 1 hour;

[0069] (3) Add a water-reducing component to the mixture after stirring in step (2), control the temperature to 40° C., and stir for 40 minutes to obtain a seventh liquid preservative F7.

[0070] Example 8

[0071] This embodiment provides a liquid preservative for concrete that resists high-concentration sulfate corrosion, which is a liquid mixture comprising the following components and weight percentages:

[0072] The expansion component is anhydrous aluminum sulfate: 5.0%, the compacting component is nano-silica: 20.0%, the hydrophobic component is amino-modified polyether siloxane: 20.0%, the water-reducing component is polycarboxylic acid water-reducing agent: 10.0%, and water: 45.0%.

[0073] It is prepared by the following method:

[0074] (1) Add water to the reaction device, control the water temperature to 40°C, add the compacting component and the swelling component to the water in sequence, and stir at a stirring speed of 450 r / min for 40 min;

[0075] (2) adding a hydrophobic component to the mixture after stirring in step (1), and then continuing to stir for 1 hour;

[0076] (3) Add a water-reducing component to the mixture after stirring in step (2), control the temperature to 30° C., and stir for 20 minutes to obtain an eighth liquid preservative F8.

[0077] Example 9

[0078] This embodiment provides a liquid preservative for concrete that resists high-concentration sulfate corrosion, which is a liquid mixture comprising the following components and weight percentages:

[0079] Expansive component anhydrous aluminum sulfate: 1.0%, dense component nano silicon dioxide: 10.0%, hydrophobic component epoxy modified polysiloxane: 10.0%, water reducing component aminosulfonate water reducing agent: 5.0%, water: 74.0%.

[0080] It is prepared by the following method:

[0081] (1) Add water to the reaction device, control the water temperature to 40°C, add the compacting component and the swelling component to the water in sequence, and stir at a stirring speed of 450 r / min for 40 min;

[0082] (2) adding a hydrophobic component to the mixture after stirring in step (1), and then continuing to stir for 1 hour;

[0083] (3) Adding a water-reducing component to the mixture after stirring in step (2), controlling the temperature to 30° C., and stirring for 20 minutes to obtain a ninth liquid preservative F9.

[0084] Example 10

[0085] This embodiment provides a liquid preservative for concrete that resists high-concentration sulfate corrosion, which is a liquid mixture comprising the following components and weight percentages:

[0086] Expansive component anhydrous aluminum sulfate: 5.0%, dense component nano silicon dioxide: 25.0%, hydrophobic component epoxy modified polysiloxane: 25.0%, water reducing component aminosulfonate water reducing agent: 10.0%, water: 35.0%.

[0087] It is prepared by the following method:

[0088] (1) Add water to the reaction device, control the water temperature to 45°C, add the compacting component and the swelling component to the water in sequence, and stir at a stirring speed of 400 r / min for 60 min;

[0089] (2) adding a hydrophobic component to the mixture after stirring in step (1), and then continuing to stir for 1 hour;

[0090] (3) Add a water-reducing component to the mixture after stirring in step (2), control the temperature to 35° C., and stir for 35 minutes to obtain a tenth liquid preservative F10.

[0091] In order to reflect the importance of each component of the liquid preservative of the present invention, the following comparative experiments were carried out.

[0092] Comparative Example 1

[0093] The purpose of this comparative example is to illustrate the effect of the absence of a bulking component on the performance of the liquid preservative.

[0094] The similarities between this comparative example and Example 1 are not described here, and only the differences from Example 1 are described. The difference between this comparative example and Example 1 is that anhydrous aluminum sulfate, an expansion component, is not used, and an equal amount of water is used instead; the rest is as described in Example 1 to obtain a first comparative liquid preservative D1.

[0095] Comparative Example 2

[0096] The purpose of this comparative example is to illustrate the effect of excess expansion component on the performance of the liquid preservative.

[0097] The similarities between this comparative example and Example 2 are not described here, and only the differences from Example 2 are described. The difference between this comparative example and Example 2 is that: 10% excess of anhydrous aluminum sulfate, an expansion component, is used, and the amount of water used is reduced accordingly; the rest is the same as described in Example 2, to obtain a second comparative liquid preservative D2.

[0098] Comparative Example 3

[0099] The purpose of this comparative example is to illustrate the effect of the lack of a compacting component on the performance of the liquid preservative.

[0100] The similarities between this comparative example and Example 3 are not described here, and only the differences from Example 3 are described. The difference between this comparative example and Example 3 is that: the dense component nano alumina is not used, but an equal amount of water is used instead; the rest is referred to as described in Example 3, and a third comparative liquid preservative D3 is obtained.

[0101] Comparative Example 4

[0102] The purpose of this comparative example is to illustrate the effect of excess dense component on the performance of the liquid preservative.

[0103] The similarities between this comparative example and Example 4 are not described here, and only the differences from Example 4 are described. The difference between this comparative example and Example 4 is that: 30% excess of dense component nano alumina is used, and the amount of water used is reduced accordingly; the rest is as described in Example 4, and the fourth comparative liquid preservative D4 is obtained.

[0104] Comparative Example 5

[0105] The purpose of this comparative example is to illustrate the effect of the lack of a hydrophobic component on the performance of the liquid preservative.

[0106] The similarities between this comparative example and Example 5 are not described here, and only the differences from Example 5 are described. The difference between this comparative example and Example 5 is that: the hydrophobic component tridecafluorooctyl triethoxysilane is not used, and an equal amount of water is used instead; the rest is the same as described in Example 5, and the fifth comparative liquid preservative D5 is obtained.

[0107] Comparative Example 6

[0108] The purpose of this comparative example is to illustrate the effect of excess hydrophobic component on the performance of the liquid preservative.

[0109] The similarities between this comparative example and Example 6 are not described here, and only the differences from Example 6 are described. The difference between this comparative example and Example 6 is that: 30% excess hydrophobic component tridecafluorooctyl triethoxysilane is used, and the amount of water used is reduced accordingly; the rest is the same as described in Example 6, and the sixth comparative liquid preservative D6 is obtained.

[0110] Comparative Example 7

[0111] The purpose of this comparative example is to illustrate the effect of the lack of a water reducing component on the performance of the liquid preservative.

[0112] The similarities between this comparative example and Example 7 are not described here, and only the differences from Example 7 are described. The difference between this comparative example and Example 7 is that: the water-reducing component polycarboxylate water-reducing agent is not used, and an equal amount of water is used instead; the rest is as described in Example 7, and the seventh comparative liquid preservative D7 is obtained.

[0113] Comparative Example 8

[0114] The purpose of this comparative example is to illustrate the effect of excess water reducing component on the performance of the liquid preservative.

[0115] The similarities between this comparative example and Example 8 are not described here, and only the differences from Example 8 are described. The difference between this comparative example and Example 8 is that: 15% of the polycarboxylate water-reducing agent, a water-reducing component, is used in excess, and the amount of water used is reduced accordingly; the rest is as described in Example 8, and the eighth comparative liquid preservative D8 is obtained.

[0116] In order to verify the performance difference between the liquid preservatives provided in the above embodiments and the comparative liquid preservatives provided in the comparative examples, the above liquid preservatives were used at a recommended dosage of 12% and subjected to a benchmark test in accordance with the performance index requirements in JC / T 1011-2021 "Concrete Anti-Corrosion Preservatives". The experimental results are shown in Table 1 below.

[0117] Table 1 Performance indexes of benchmark tests for various liquid preservatives

[0118]

[0119]

[0120] According to the experimental results in the benchmark test in Table 1, it can be preliminarily determined that the liquid preservative provided by the present invention needs to meet the current industry standard JC / T 1011-2021 "Concrete Anti-Corrosion Preservative", and the range of each component therein is preliminarily determined. The specific results and conclusions are as follows:

[0121] (1) Expansion component

[0122] The expansion component has a significant impact on the 1d expansion rate index of the liquid preservative product. If the preservative product needs to meet the 1d expansion rate index of JC / T 1011-2021 "Concrete Anti-Corrosion Preservative", the expansion component content should not be less than 1.0%.

[0123] (2) Dense component

[0124] The dense component has a significant impact on the compressive strength ratio index of the liquid preservative product. When the dense component content exceeds 10%, the 7d and 28d compressive strength ratios both meet the performance index requirements of JC / T 1011-2021 "Concrete Anti-Corrosion Preservative". In addition, when the dense component content exceeds 10%, the corrosion resistance coefficient in the benchmark test is significantly improved, and the chloride ion diffusion coefficient ratio is significantly reduced, indicating that the addition of dense components can reduce the transmission of harmful ions and enhance the corrosion resistance of cement-based materials. Therefore, if the liquid preservative product needs to meet the compressive strength ratio and corrosion resistance indicators of JC / T 1011-2021 "Concrete Anti-Corrosion Preservative", the dense component content should not be less than 10.0%.

[0125] (3) Hydrophobic component

[0126] The increase of hydrophobic components has a certain negative impact on the compressive strength ratio index of the liquid preservative product. When the content of hydrophobic components exceeds 25%, the 7d and 28d compressive strength ratios do not meet the performance index requirements of JC / T 1011-2021 "Concrete Anti-Corrosion Preservative"; and when the content of hydrophobic components is less than 10%, the corrosion resistance coefficient index in JC / T1011-2021 "Concrete Anti-Corrosion Preservative" does not meet the requirements. Therefore, if the liquid preservative product needs to meet the compressive strength ratio and corrosion resistance index of JC / T 1011-2021 "Concrete Anti-Corrosion Preservative", the content of hydrophobic components should be between 10.0% and 25.0%.

[0127] (4) Water reducing component

[0128] The increase of water-reducing components can improve the compressive strength ratio index of the liquid preservative product. When the content of water-reducing components exceeds 5.0%, the 7d and 28d compressive strength ratios meet the performance index requirements of JC / T 1011-2021 "Concrete Anti-Corrosion Preservatives"; and when the content of water-reducing components is greater than 10%, the corrosion resistance coefficient index in JC / T 1011-2021 "Concrete Anti-Corrosion Preservatives" does not meet the requirements. In summary, if the liquid preservative product needs to meet the compressive strength ratio and corrosion resistance index of JC / T 1011-2021 "Concrete Anti-Corrosion Preservatives", the content of water-reducing components should be between 5.0% and 10.0%.

[0129] In addition, the effects of the above-mentioned liquid preservatives when used in concrete were tested to determine the upper limits of the expansion component and the compaction component. At the same time, the synergistic effect between the components under the erosion of high-concentration sulfates in concrete also needs to be further verified. Therefore, F2, F4, F9, F10, D2, D4, and D5 were selected according to the concrete mix ratio in Table 2 below, and the performance indicators under the dry-wet cycle of 15% sodium sulfate solution were comprehensively compared to determine the efficacy and reasonable composition range of each component.

[0130] It should be noted that, generally speaking, for sulfate environments with concentrations higher than 100,000 mg / L, according to current specifications, C50 concrete strength grade is recommended.

[0131] Table 2 Concrete mix ratio (kg / m 3 )

[0132]

[0133] According to the sulfate dry-wet cycle test in GBT 50082-2019 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the mass fraction of sodium sulfate solution was adjusted to 15% for dry-wet cycle. After each concrete has undergone a certain number of sulfate dry-wet cycles, the compressive strength and corrosion resistance coefficient of the concrete are tested. The test results are shown in Table 3 below.

[0134] Table 3 Corrosion resistance coefficient of compressive strength of concrete under dry-wet cycle of 15% sodium sulfate solution

[0135]

[0136] From the data in Table 3 above, we can see the variation law of the compressive strength and corrosion resistance coefficient of each concrete under the dry-wet cycle of 15% sodium sulfate solution. Specifically, it can be seen that the blank group without preservatives does not meet the requirement of 150 dry-wet cycles in GBT50082-2019 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete".

[0137] Comparing the C-F2 (containing 5.0% of the expansion component) and C-D2 (containing 10.0% of the expansion component) groups, it can be found that when the expansion component exceeds 5.0%, the compressive strength corrosion resistance coefficient of the concrete decreases significantly after more than 120 dry-wet cycles of the 15% sodium sulfate solution, and the sulfate content inside the concrete increases significantly. This shows that when the expansion component is too high, the internal density of the concrete increases, and the invasion of sulfate ions can be organized in the early stage of the 15% sodium sulfate solution erosion. When a sufficient amount of sulfate invades, it reacts with the hydration product to produce expansive corrosion products, which will cause cracking inside the concrete under the action of expansion stress, and will aggravate the sulfate erosion of the concrete in the later stage. Therefore, the expansion component should not exceed 5.0%. Similarly, comparing the C-F4 (containing 25.0% of the dense component) and C-D4 (containing 30.0% of the dense component) groups, when the dense component exceeds 25.0%, the sulfate erosion of the concrete in the later stage will be aggravated. Therefore, the dense component should not exceed 25.0%.

[0138] The hydrophobic component plays an important role in the concrete's resistance to high-concentration sulfate erosion. When the liquid preservative component does not contain the hydrophobic component (C-D5), the compressive strength corrosion resistance coefficient of the concrete is significantly lower than that of C-F9 and C-F10, and does not meet the requirement of 150 dry-wet cycles in GBT50082-2019 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The reason is that the hydrophobic component significantly reduces the water absorption rate of the concrete matrix, thereby reducing the risk of sulfate ions invading the concrete and causing damage.

[0139] While the invention has been shown and described with reference to the particular embodiments, it will be understood by those skilled in the art that various changes in form and details may be made therein without departing from the spirit and scope of the invention as defined by the claims and their equivalents.

Claims

1. A liquid preservative for concrete that resists high-concentration sulfate corrosion, characterized in that: It is composed of the following components mixed evenly in liquid form according to mass fraction: Expansion component 1.0%~5.0%; Dense component 10.0%~25.0%; Hydrophobic component 10.0%~25.0%; Water reducing component 5.0%~10.0%; Water balance; Among them, the expansion component is anhydrous aluminum sulfate and / or anhydrous magnesium sulfate, the dense component is nano silicon dioxide and / or nano aluminum oxide, the particle size of the dense component is less than 50 nm, and the hydrophobic component is at least one of epoxy-modified polysiloxane, amino-modified polyether siloxane, and tridecafluorooctyl triethoxysilane.

2. The liquid preservative according to claim 1, characterized in that The water reducing component is a polycarboxylate water reducing agent and / or an aminosulfonate water reducing agent.

3. The method for preparing a liquid preservative according to claim 1 or 2, characterized in that: Includes steps: S1. Mix the compacting component and the expanding component in water and mix them evenly at 30℃~50℃; S2, adding a hydrophobic component to the mixed solution obtained in step S1 and mixing evenly; S3. Add a water-reducing component to the mixed solution obtained in step S2, and mix evenly at 25° C. to 40° C. to obtain the liquid preservative.